2009
DOI: 10.1016/j.ejso.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound and fine needle aspiration cytology of the axilla in the pre-operative identification of axillary nodal involvement in breast cancer

Abstract: To cite this version:C Swinson, D. Ravichandran, M. Nayagam, S Allen. Ultrasound and fine needle aspiration cytology of the axilla in the pre-operative identification of axillary nodal involvement in breast cancer. EJSO -European Journal of Surgical Oncology, WB Saunders, 2009, 35 (11) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 14 publications
3
52
0
Order By: Relevance
“…Various studies have reported the sensitivity and specificity rates of FNAB between 25-95% and 97-100%, respectively (8,14,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). False positive results has been reported around 1.4-1.6% (20,23,30), and false negative rates as 8-12% (15,23,24,26,(29)(30)(31).…”
Section: Factors Influencing Sensitivity and Specificity Ratesmentioning
confidence: 99%
“…Various studies have reported the sensitivity and specificity rates of FNAB between 25-95% and 97-100%, respectively (8,14,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). False positive results has been reported around 1.4-1.6% (20,23,30), and false negative rates as 8-12% (15,23,24,26,(29)(30)(31).…”
Section: Factors Influencing Sensitivity and Specificity Ratesmentioning
confidence: 99%
“…Ultrasound is neither sufficiently sensitive nor specific to be used alone; in patients with indeterminate cortical thickening in the range of 2-4 mm, it is essential to assess whether such patients have involved nodes by FNAC or core biopsy. [20][21][22][23] The majority of surgeons continue to perform ANC which is an appropriate treatment for involved axillary nodes. Axillary radiotherapy is another option for involved nodes, and this is used in some centres and has been shown to produce good long-term disease control rate.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is the method of choice for the initial evaluation of the axilla in patients with a diagnosis of carcinoma [13], and allows the initial characterization of symptomatic lesions in young women.…”
Section: Breast Ultrasoundmentioning
confidence: 99%